Pengaruh Suku Bunga Bank Indonesia Stabilitas Keuangan dan Pertumbuhan Terhadap Kinerja Bank - Rizky Andriansyah; Bahtiar Usman, Henny Setyo Lestari, Catur Rahayu Martiningtiyas, Anita Roosmalina Matusin (YUME : Journal of Management, 2025)
This study aims to analyze the determinants of profitability of banking sector companies in Indonesia. Profitability is measured using return on assets (ROA). Independent variables and control variables include Bank Indonesia interest rates, revenue growth rate, financial stability, capital adequacy, bank size, and leverage. The study used a sample of 215 data from 43 companies for 5 years, with purposive sampling technique. The test method used panel data regression using E-views 9 software. The results showed that revenue growth rate, capital adequacy, and bank size had a positive effect on ROA and other variables showed no effect on ROA. The results of this study are expected to provide implications for financial managers by considering the level of revenue growth rate, capital adequacy, dan bank size through optimizing quality lending, ensuring that core capital and supplementary capital remain strong, and encouraging healthy and sustainable growth in bank assets in order to increase bank profitability. Keywords:Return on assets, Revenue Growth Rate, Capital Adequacy, Bank Size, Profitability